The Papers of William Penn, Volume 2 : 1680-1684 - Landsman, Ned C., 1951-; Soderlund, Jean R., 1947-; Ryerson, Richard Alan, 1942-; Wilds, Scott M.; Dunn, Mary Maples; Dunn, Richard S. (Book collections on Project MUSE., 2016)
This volume, covering the years 1680 to 1684, documents the founding of Pennsylvania.